Molecular structure and vibrational spectra of 2(5H)-furanone and 2(5H)-thiophenone isolated in low temperature inert matrix - Breda, S. (2008)
The structure and vibrational spectra of two five-membered heterocyclic [alpha]-carbonyl compounds have been studied. The experimental FTIR spectra 2(5H)-furanone and 2(5H)-thiophenone monomers isolated in inert argon matrices at 10 K are reported and discussed. The interpretation of the experimental data is supported by vibrational calculations at the MP2 and DFT(B3LYP) levels of theory with the 6-311++G(d,p) basis set. Spectra/structure correlations were extracted from the data calculated for the two title compounds and for their six-membered ring analogues, [alpha]-pyrone and thiapyran-2-one. The vibrational frequencies of the CO, CC, CH and CH2 moieties were correlated with the ring size, atomic charges and the nature of heteroatom. Natural bond orbital analysis revealed important details of the electronic structure and dominant intramolecular interactions in 2(5H)-furanone and 2(5H)-thiophenone and provided an additional insight into their vibrational spectra.